A Case of Incidentally Detected Bladder Lipoma and a Review of the Literature - Emekli, Emre; Gündoğdu, Elif (Current Medical Imaging, 2022)
Background: Lipomas are benign fatty tumors made of fat tissue. Bladder lipomas are extremely rare. For this reason, it is necessary to be aware of the imaging features when incidentally detected in imaging. Case Report: In the abdominal Computed Tomography (CT) performed as part of the follow-up examination of a 43-year-old patient, who had undergone surgery for adrenal adenoma five years earlier, a 14x9x8 mm smoothly marginated, ovoid-shaped, hypodense mass lesion with a homogeneous internal structure was detected in the anterior bladder wall. The pre-contrast density of the lesion was measured as -105 HU. The magnetic resonance imaging performed one year after the CT examination revealed a 14x9x8 intramural mass in the bladder wall, showing protrusion toward the lumen. The mass was observed to be markedly hypointense on fat-suppressed T1 and T2-weighted images and considered to be consistent with a bladder lipoma. Discussion: Bladder lipomas are benign lesions that can vary in clinical presentations but usually cause hematuria. In imaging, bladder lipomas are present as homogeneous lesions containing macroscopic fat. The differential diagnosis of bladder lipomas includes other mesenchymal rare benign tumors that can arise from the submucosal layer of the urinary bladder including leiomyoma, hemangioma, plasmacytoma, fibroma, and neurofibroma. Only the liposarcoma and pelvic lipomatosis could show similar features. The less differentiated liposarcomas tend to present more heterogeneous enhancement, irregular-shaped margins, and infiltrative behaviour. Also, appropriate multiplanar reconstructions may allow the radiologist to determine if it is an extravesical pelvic lipomatosis. Conclusion: Using CT and MRI, the lesions that are rich in adipose tissue can be distinguished from other lesions, and their diagnosis can be made to a great extent. However, a histopathological examination is required for a definitive diagnosis.
Keywords: incidental finding